Perceptions of respiratory tract infections and their implications for disease prevention practices among older adults in Mysuru, India. - Jantine Marly van Wijlick; K S Sahana; B S Jayaraj; Christopher Pell; Gangadhar Mysore Rajagopal; P A Mahesh (PLOS Global Public Health, 2025)
Respiratory tract infections (RTIs) remain an important cause of mortality and morbidity, particularly among older adults. Annual influenza epidemics cause around 127,000 deaths in India of which 65% are among adults of 65 years and older. Because of India's rapidly growing older adult population, RTIs are likely to become an even greater public health issue and implementing effective preventive strategies will be crucial. To inform pharmaceutical and non-pharmaceutical prevention strategies for RTIs among older adults, this study explored the perceptions of RTIs and their implications for disease preventive practices of older adults visiting a tertiary hospital in Mysuru, India. Qualitative research methods, including structured observations and in-depth interviews with older adults and healthcare workers were used. Deductive and inductive analysis highlighted how common colds and influenza infections were regarded as inevitable and not considered severe illnesses by older adults. Whereas COVID-19 prompted fear because of severe illness episodes and sudden deaths among family members. Common colds and influenza were often related to eating 'cold' food and a 'cold' environment, and preventive measures reflected these beliefs. Language played a significant role in the understandings of RTIs in older adults. Different terms for influenza, common cold and vaccination in Kannada and English could lead to lack of awareness of preventive measures including vaccination for RTIs. Because of campaigns during the COVID-19 pandemic, older adults were familiar with non-pharmaceutical prevention techniques such as hand hygiene and social distancing. In conclusion, using relatable medical terms when providing information about RTI prevention and the possibility of taking a holistic approach towards prevention and healthy aging including diet, vaccination and non-pharmaceutical practices means that those are more likely to resonate among the targets. To promote preventive practices, those would ideally also describe the health risks of common RTIs.